Italian conservatory in the context of modern musical life - Ponomarenko, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. The Italian Conservatory has always been the center of the musical life in the country, it attracts musicians from all over the world and thus ensures a high level of musical education. Innovations are combined here with traditional teaching methods, classical methods with the latest ones, which determines the modern level of its activities. The conservatory in modern Italy is not only an educational institution, but also a sociocultural institution that establishes extensive social connections, actively implements modern methods of work, opens up relevant scientific and educational areas, updates specialties and specializations, and also develops cultural ties, developing and implementing various musical projects. This is facilitated by the intensive development of cooperation and interaction with various socio-cultural institutions — the opera house, the museum, the music festival, which significantly affects the promotion of cities and regions with the help of special events (concerts, festivals, cultural events). Main objective. The goal of the study is to reveal the activities of the Italian Conservatory as a multifunctional institution, in particular to characterize the model of integration of art and education as the basis for its development in modern conditions. Methodology of the study. Since the Italian Conservatory is considered in the article not only as an educational institution, the specifics of its functioning in the socio-cultural context are of scientific interest: concert and educational activities, organization of musical projects. Such a conceptual approach implies the use of a complex of scientific methods: historical, analytical, empirical, socio-cultural, inductive, deductive, systemic, generalization. Results and conclusions. The activities of the Italian Conservatory as a multifunctional institution are aimed at preserving and developing artistic traditions, as well as updating the modern educational process by developing innovative scientific and educational projects, opening new specialties and specializations. Its experience will also be of interest to Ukrainian musicians, especially in terms of interaction with various sociocultural institutions in the preparation and implementation of cultural, artistic, musical projects together with the opera house, museum, and music festivals. This will lead to the popularization of the creativity of individual artists, performing groups, scientific and artistic schools, as well as the promotion of cities and regions of the country with which their creative activity is associated.